PD-L1 expression is regulated by both DNA methylation and NF-kB during EMT signaling in non-small cell lung carcinoma. (4th May 2018) - Asgarova, A.; Asgarov, K.; Godet, Y.; Peixoto, P.; Nadaradjane, A.; Boyer-Guittaut, M.; Galaine, J.; Guenat, D.; Mougey, V.; Perrard, J.; Pallandre, J. R.; Bouard, A.; et al.
ABSTRACT: Tumor cells, which undergo Epithelial-mesenchymal transition (EMT) acquire increased capacities of proliferation, invasion and have the ability to generate metastases by escaping the immune system during their systemic migration. To escape the immune system, cancer cells may induce tolerance or resist elimination by immune effectors via multiple mechanisms and we hypothesized that EMT may control the expression of immune checkpoint inhibitors, then promoting immune evasion. PD-L1 (programmed cell death ligand 1) but not PD-L2 nor Galectin 9 or Death receptor (DR4, DR5 and Fas) and ligands (FasL and TRAIL) expression was up-regulated during cytokine-driven EMT in a reversible manner. Moreover PD-L1 is overexpressed in VIMENTIN positive NSCLC tissues. We also demonstrated that the expression of PD-L1 required both TNFα and TGFβ1. Indeed, TGFβ1 decreased DNMT1 content and that resulted in PD-L1 promoter demethylation whereas TNFα induced the NF-κB pathway that promoted expression of demethylated PD-L1 promoter.